A juvenile ALS‐like phenotype dramatically improved after high‐dose riboflavin treatment. Issue 2 (5th February 2020) - Carreau, Christophe; Lenglet, Timothée; Mosnier, Isabelle; Lahlou, Ghizlene; Fargeot, Guillaume; Weiss, Nicolas; Demeret, Sophie; Salachas, François; Veauville‐Merllié, Alice; Acquaviva, Cécile; Nadjar, Yann
Abstract: Riboflavin transporter deficiency (RTD) was recently characterized as a cause of genetic recessive childhood‐onset motor neuron disease (MND) with hearing loss, formerly described as Brown‐Vialetto‐Van‐Lear syndrome. We describe a 18‐year‐old woman with probable RTD mimicking juvenile Amyotrophic Lateral Sclerosis (ALS) who presented with an inaugural respiratory failure and moderate distal four limbs weakness. Only one heterozygous SLC52A3 mutation was detected, but presence of a sub‐clinical auditory neuropathy and dramatic improvement under high dose riboflavin argued for a RTD. As RTD probably has a larger phenotypic spectrum than expected, a high dose riboflavin trial should be discussed in young‐onset MND.